2006
DOI: 10.1002/dmrr.648
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in diabetic nephropathy — cause or consequence?

Abstract: Insulin resistance (IR) is associated with multiple risk factors for cardiovascular disease. Many studies have shown that IR is present in chronic renal failure (CRF), and recent evidence suggests that IR can also occur in the early stages of renal disease. Patients with diabetic nephropathy (DN) have an increase in cardiovascular mortality, and since IR may be a contributing factor, this emphasizes the importance of a detailed understanding of the mechanisms linking IR and renal dysfunction at different stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 142 publications
3
21
0
Order By: Relevance
“…So, PTX-3 was the only parameter related to the disease stage and proteinuria in our study by mechanisms that we could not be able to explain. Our study also supports the studies showing increased insulin resistance in CKD patients since serum insulin, C-peptide and HOMA-IR were significantly increased in lower GFR groups 31 ( Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…So, PTX-3 was the only parameter related to the disease stage and proteinuria in our study by mechanisms that we could not be able to explain. Our study also supports the studies showing increased insulin resistance in CKD patients since serum insulin, C-peptide and HOMA-IR were significantly increased in lower GFR groups 31 ( Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…Insulin resistance and compensatory hyperinsulinemia are common in both diabetic and nondiabetic CKD patients and increase as the GFR decreases over the course of the disease [133,134]. Evidence exists that insulin resistance and elevated circulating plasma insulin levels cause sympathetic activation, impaired BRS, and hypertension or potentiate the hypertensive effects of other pressor agents, including Ang II [135,136].…”
Section: Insulinmentioning
confidence: 98%
“…Apolipoprotein (apo) B48, a major component of chylomicron, is also increased in diabetes, suggesting an accumulation of chylomicron remnants [11]. It has been demonstrated that insulin resistance is aggravated along with the progression of DN, even in the early stage of microalbuminuria [12]. An elevation in the serum levels of apoC-III, an inhibitor of LPL, is also observed in subjects with DN [3].…”
Section: Etiology and Epidemiology Of Diabetic Dyslipidemiamentioning
confidence: 99%